Bosea rubneri sp. nov. Isolated from Organically Grown Allium cepa - Dominic A. Stoll; Christina Grimmler; Birgit Hetzer; Alexandra Masoura; Sabine E. Kulling; Melanie Huch (Current Microbiology, 2024)
Strain ZW T0_25 T was isolated from an onion sample ( Allium cepa var. Hytech F1) within a storage trial and proofed to be a novel, aerobic, Gram-stain negative, rod-shaped bacterial strain. Analyses of the 16S rRNA gene sequence and of the whole draft genome sequences, i.e., digital DNA–DNA hybridization (dDDH), Average Nucleotide Identity (ANI) and Average Amino Acid Identity (AAI) showed that this strain represents a new species of the genus Bosea . The genome size of strain ZW T0_25 T is 6.19 Mbp, and the GC content is 66.9%. As whole cell sugars, rhamnose, ribose and glucose were identified. Ubiquinone Q-10 is the major respiratory quinone with 97.8%. Polar lipids in strain ZW T0_25 T are composed of one phosphatidylethanolamine, one phosphatidylglycerol, one aminophospholipid, two aminolipids, one glycolipid and two phospholipids whereas the fatty acid profile predominantly consists of C18:1 w7c (63.3%), C16:1 w7c (19.5%) and C16:0 (7.1%). Phenotypic traits were tested in the wet lab as well as predicted in silico from genome data. Therefore, according to this polyphasic approach, the new name Bosea rubneri sp. nov. with the type strain ZW T0_25 T (= DSM 116094 T = LMG 33093 T ) is proposed.